Cross-Sectional Study on Health Literacy and Internet Accessibility Among Patients With DM in Gansu, China - Zhao, Na; Luo, Xifeng; Zhang, Hailiang; Dai, Runjing; Pan, Weimin; Hambly, Brett D.; Bao, Shisan; Zhu, Xiangdong; Fan, Jingchun (Frontiers in Public Health, 2021)
Objective: To determine the relationship between health literacy of patients with Diabetes Mellitus (DM) and the accessibility of internet surfing for information concerning DM. Methods: A multi-stage stratified sampling method was utilized to conduct a questionnaire survey on DM health literacy and internet accessibility among 1,563 patients with DM in Gansu Province in 2020. Logistic regression was performed to analyze the factors that influence health literacy and internet accessibility; while the chi-square test was used to compare the differences in needs. Results: Among 1,563 valid questionnaires collected with an effective rate of 95.7%, there were 65.4%, 66.3% or 51.1% of patients with DM that were found to have good health knowledge, attitudes or practice levels, respectively. Occupation, income, disease course of DM and accessibility to the internet were the main factors influencing health literacy. Age, residency, occupation, education, income and family history of DM were the factors influencing accessibility to internet surfing for DM. The expectations from patients with DM for the capacity to obtain DM information from traditional sources or through internet sources was 1,465 (93.7%) or 1,145 (73.3%), respectively. Patients with DM had a 2-fold higher desire to obtain DM health information from internet media if the patients had access to the internet than those without (P<0.05). Conclusions: The socioeconomic status and access to the internet were the main contributing factors for health literacy, as socioeconomic status is closely related to access to the internet.